"Postcolonial Disaster": Purdah, Precarity, and Hunger in Abu Ishaque's Surja Dighal Bari (The Ominous House). Issue 1 (2nd January 2023) - Bhattacharya, Sourit
Abstract: The 1943 Bengal famine had severely changed the social landscape in rural Bengal. Thousands of peasants who mortgaged or sold their lands to the economic elite to migrate to Calcutta for food had to start over landless and precarious. Married women who were forcibly repudiated by their husbands ("talaq") during the famine had to abide by the religious law of purdah (of keeping women at home) and accepting death by hunger. Abu Ishaque's 1955 novel, Surja Dighal Bari (The Ominous House) evocatively captures these harrowing moments of hunger and poverty in the majority rural population through the life-events of Jaigun and her family. The novel shows how a resilient single mother's will to work and provide for her children is crushed by the male elite through religious injunctions and social alienation. In this essay, I will comment on the intersection of land, hunger, purdah, and patriarchy, reading them together as an instance of "postcolonial disaster, " which conspires to produce an endless condition of precarity for the socio-economically vulnerable in post-independence rural East Pakistan, and consequently a raw esthetic of realism in the postcolony.